A general approach to fabricate free-standing metal sulfide@carbon nanofiber networks as lithium ion battery anodes. Issue 7 (10th December 2015) - Fei, Ling; Williams, Brian Patrick; Yoo, Sang Ha; Carlin, Joseph Michael; Joo, Yong Lak
Abstract : Fabrication of free-standing metal sulfide@CNF electrodes for lithium ion batteries. Abstract : A general approach for fabricating free-standing metal sulfide and carbon nanofiber mats is developed via electrospinning, starting with cheap and abundant raw materials. The prepared free-standing samples have metal sulfide nanoparticles dispersed throughout the interconnected carbon fibers. When applied to LIB, the composites demonstrate excellent cyclability and rate capability.